Study on the effect of intracoronary Adenosine on the incidence of myonecrosis after elective percutaneous coronary intervention - Ahsan, Md Razib; Siddique, Md Abu; Haque, KMHS Sirajul; Ahsan, Syed Ali; Ahmed, Md Khurshed; Rahman, Md Mukhlesur (University Heart Journal, 2009)
Appearance of serum creatine kinase MB fraction (CK-MB), reflecting the periprocedural myonecrosis, after successful percutaneous coronary intervention (PCI) is associated with future cardiac adverse events. The intracoronary adenosine on the incidence of myonecrosis after elective PCI was assessed. In this prospective, case control study with a total of 60 patients, 30 cases pretreated with 50 micro grams bolus intracoronary adenosine before advancement of guidewire and 30 controls not pretreated was studied during elective PCI. Both groups received statin and loading dose of Clopidogrel. Myonecrosis was assessed by CK-MB level after PCI. Post procedural myonecrosis occurred in 16.7 % (n=5) in case group and 36.7 % (n=11) in control group (OR=1.818; 95% CI 0.841; P=0.080). The result is not statistically significant but shows that the incidence of myonecrosis was reduced from 36.7% to 16.7%. Intracoronary adenosine reduces the incidence of myonecrosis after elective PCI. Keywords: Adenosine; Creatine kinase MB fraction; Intracoronary; Myonecrosis; Percutaneous coronary intervention; Periprocedural. Â  doi:10.3329/uhj.v4i2.2068 University Heart Journal Vol. 4 No. 2 July 2008 p19-23